Efficacy, safety, and impact on hospitalizations of paliperidone palmitate in recent-onset schizophrenia - Zhang F (Dove Medical Press, 2015)
Fan Zhang,1 Tianmei Si,2,3 Chiun-Fang Chiou,4 Anthony WF Harris,5 Chang Yoon Kim,6 Padmashree Jahagirdar,7 Steve Ascher8 1Xian Janssen Pharmaceuticals, Beijing, People’s Republic of China; 2Department of Clinical Psychopharmacology, Peking University Institute of Mental Health, Beijing, People’s Republic of China; 3Key Laboratory of Mental Health, Ministry of Health (Peking University), Beijing, People’s Republic of China; 4Janssen Asia-Pacific, Singapore; 5Discipline of Psychiatry, Sydney Medical School, University of Sydney, Australia and Brian Dynamics Center, Westmead Millennium Institute for Medical Research, Westmead, NSW, Australia; 6Asan Medical Center, University of Ulsan College of Medicine, Seoul, South Korea; 7Theorem Clinical Research, Bangalore, India; 8Janssen Research and Development, LLC, Titusville, NJ, USA Objective: To evaluate the efficacy, safety, and impact on hospitalizations of long-acting injectable paliperidone palmitate (PP) treatment, in patients with recent-onset schizophrenia who had not responded satisfactorily to oral antipsychotics.Methods: In this 18-month, open-label, Phase-IIIb study from Asia-Pacific region, patients (18–50 years) with recent-onset (≤5 years) schizophrenia unsatisfactorily treated with previous oral antipsychotics were initiated on PP 150 mg eq on day 1, 100 mg eq on day 8, followed by flexible once monthly maintenance doses of 50–150 mg eq. The number and duration of hospitalizations were compared using a mirror analysis method between two periods: retrospective (12 months before PP initiation) and prospective (12 and 18 months after PP treatment) periods.Results: A total of 303 out of 521 (58%) patients (mean age, 28.7 years; 65.5% men, 92.5% Asian) completed the study. Positive and Negative Syndrome Scale (PANSS) total score improved significantly from baseline to month 18 (mean [standard deviation, SD] change: -11.3 [21.38], P<0.0001, primary endpoint). Subgroup analysis revealed greater improvements among patients with worse disease severity at baseline: PANSS ≥70 versus <70 (mean [SD] change: -23.1 [24.62] vs -4.7 [15.98], P<0.0001 each). Secondary efficacy endpoints such as Clinical Global Impression of Schizophrenia (CGI-SCH), Medication Satisfaction Questionnaire (MSQ) scores showed significant improvements (P<0.0001) from baseline; 33.3% patients achieved symptom remission. In mirror analyses set (N=474), PP significantly (P<0.0001) reduced mean number of hospitalization days/person/year (12-month: 74.3 vs 19.7; 18-month: 74.3 vs 18.9) as well as percentage of patients requiring hospitalization in past 12 months (12-month: 39.7% vs 24.6%; 18-month: 39.7% vs 25%), and PP treatment increased the proportion of patients not requiring hospitalization (12-month: 60.3% vs 75.4%; 18-month: 60.3% vs 75%) from retrospective to prospective period. Adverse events (≥15%) were extrapyramidal symptoms-related (31.3%), injection-site pain (18.6%), and insomnia (15.2%).Conclusion: PP was efficacious and generally tolerable with significant reductions observed in both number of hospitalizations and days spent in hospital.Trial registration number: ClinicalTrials.gov: NCT01051531. Keywords: atypical antipsychotics, long-acting injectables, open-label, paliperidone palmitate, schizophrenia